2018
DOI: 10.1177/0301006618767258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Facial Skin Smoothness and Blemishes on Trait Impressions

Abstract: People make trait inferences based on facial appearance, and these inferences guide social approach and avoidance. Here, we investigate the effects of textural features on trait impressions from faces. In contrast to previous work, which exclusively manipulated skin smoothness, we manipulated smoothness and the presence of skin blemishes independently (Study 1) and orthogonally (Study 2). We hypothesized that people are particularly sensitive to skin blemishes because blemishes potentially indicate poor health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 51 publications
1
48
0
Order By: Relevance
“…Given the importance of avoiding unhealthy individuals (Schaller & Duncan, 2007;Zebrowitz et al, 2003;Zebrowitz & Rhodes, 2004), we would therefore expect the negative effect of low attractiveness to be stronger than the positive effect of high attractiveness (cf. Jaeger, Wagemans, et al, 2018;Pazda et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the importance of avoiding unhealthy individuals (Schaller & Duncan, 2007;Zebrowitz et al, 2003;Zebrowitz & Rhodes, 2004), we would therefore expect the negative effect of low attractiveness to be stronger than the positive effect of high attractiveness (cf. Jaeger, Wagemans, et al, 2018;Pazda et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Facial attractiveness is strongly correlated with perceptions of health (Jaeger, Wagemans, Evans, & van Beest, 2018;Pazda, Thorstenson, Elliot, & Perrett, 2016;Rhodes, 2006). Since people should be particularly motivated to avoid unhealthy (and therefore unattractive) individuals (Schaller & Duncan, 2007;Zebrowitz, Fellous, Mignault, & Andreoletti, 2003;Zebrowitz & Rhodes, 2004), this account would predict an ugliness penalty, but not necessarily a beauty premium.…”
Section: The Current Studymentioning
confidence: 99%
“…The sexual dimorphism results indicated that while masculinity is clearly not preferred in female faces (d = 1.00), neither is increased femininity (d = .34). As the forced choice paradigm can only establish relative preferences, research teasing apart the direction of manipulation effects have often found that participants exhibit a relative preference for the unmanipulated stimuli to the 'decreased' version, rather than a preference for the 'increased' version [68,69,76]. That is, rather than preferring increased femininity in faces, participants dislike masculinity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, between-face variability is a large source of variance when compared to manipulations [73][74][75]. Recent efforts have modelled this stimulus variation as a random effect using linear mixed models, finding modest effects of important factors like skin condition on attractiveness [76]. These approaches are capable of quantifying the variance that arises from faces and participants, which is necessary because some participants may give lower or higher average ratings irrespective of the faces they see.…”
Section: Ratings Studiesmentioning
confidence: 99%